2nd International Conference On Sustainable Development Goals. ICSD 201 Achieving SDCs : Rising to the Challenge (Programme Book) - Wong, Swee Kiong; Tan, Su Jin (2019)
The International Conference on Sustainable Development Goals is an international conference that focuses on 17 goals of Sustainable Development Goals (SDGs). The event is introduced to support the implementation of the new agenda of the United Nations on September 2015.